The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10020307
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Intra- versus Extra-Corporeal Ileocolic Anastomosis after Minimally Invasive Right Colectomy for Cancer: An Observational Study

Abstract: Intracorporeal anastomoses (IA) are increasingly being used in colorectal surgery. Some data suggest that these might confer benefits compared with extracorporeal anastomoses (EA). The aim of this study is to compare the short-term complications associated with IA versus EA for minimally invasive right colectomy. This is a single-centre, retrospective study on a prospective database. Patients who underwent minimally invasive right colectomy for cancer between January 2017 and December 2019 were assessed for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In our study after PSM, the ECA group showed slightly greater overall morbidity than the ICA group (52.4% vs 19% respectively), but it was not statistically significant (p=0.052). Other studies showed similar results (18,19). In our study, we did not find a statistically significant difference in anastomotic leakage between the two groups, which is consistent with other studies (15,20,21).…”
Section: Conclusion Conclusionsupporting
confidence: 93%
“…In our study after PSM, the ECA group showed slightly greater overall morbidity than the ICA group (52.4% vs 19% respectively), but it was not statistically significant (p=0.052). Other studies showed similar results (18,19). In our study, we did not find a statistically significant difference in anastomotic leakage between the two groups, which is consistent with other studies (15,20,21).…”
Section: Conclusion Conclusionsupporting
confidence: 93%
“…Lastly, intracorporeal anastomosis, compared with the extracorporeal approach, not only has similar rates of anastomotic leak but has also been shown to lower the risk for global, medical and surgical complications, SSI and wound complications, including the rate of incisional hernias, and to shorten the hospital stay [ 2 , 12 , 13 , 14 ].…”
Section: Comparison With Other Methods Advantages and Disadvantagesmentioning
confidence: 99%
“…There is no consensus on any differences in outcomes based upon these variations [3][4][5][6][7][8][9][10][11]. Therefore, we aimed to assess the impact of the type of stapler used in stapled ileocolic anastomosis on postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There is a variety of staplers that can be used for the construction of stapled ileocolic anastomosis that differ in length and height. There is no consensus on any differences in outcomes based upon these variations [3–11]. Therefore, we aimed to assess the impact of the type of stapler used in stapled ileocolic anastomosis on postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%